Control of caterpillar Spodoptera frugiperda (Smith, 1797) in different technologies Bts (Bacillus thuringienses) in maize crop - Soares Barcelos, Paulo Henrique [UNESP]; Angelini, Marina Robles (Univ Estadual Mato Grosso Sul, 2018)
The genetically modified maize containing the Bt gene is a rising from the bacterium, Bacillus thuringienses and is used to control lepidopteran. Thus, the aim of this study was to evaluate the efficacy of different Bt technology for the control of the Spodoptera frugiperda. The experimental design was a randomized block with six treatments and four replications. 7, 14, 21 and 28 days after emergence (DAE) evaluated visual damage on the leaves caused by S. frugiperda, where 25 plants per plot, were evaluated according to visual scale of damage. The assessment of the number of larvae on the cartrige was performed weekly 7 to 28 sampling AED 10 plants per plot, counting the number of small larvae (< 1.5 cm) and large (> 1.5 cm) present in the cartridge. The averages of the visual damage scores of the Bt technologies were lower when compared to the conventional hybrid means at 7 and 14 DAE. At 21 DAE, the Optimum Intrasect technology did not differ from conventional maize, and at 28 DAE the same result was observed as in Herculex technology. At 7 DAE, plants with no damage (note 0) or slight damage (note 1) predominated in the experiment area. From 14 DAE scores above or equal to 3 were observed in the treatments Herculex, Optimum Intrasect, Powercore, VT Pro and conventional, and the percentage of plants with incidence of notes above 3 were higher than 20% only in Herculex treatments, Optimum Intrasect and conventional. The Powercore technology (2B587PW) and Viptera3 (Impact) presented effective in the culture of protectionin relation to the S. frugiperda.
Keywords: Integrated pest management; Lepidoptera; Zea mays L.